Table of Content - - (Journal of medical and pharmaceutical sciences, 2024)
Table of Content: 1. Effect of beetroot extract on glucose-6-phosphate dehydrogenase, red blood cells, and their aggregation in a patient with Hereditary Spherocytosis: A case report Dr. Zahraa S. Al-Garawi, Saif A. Mahnna, Bilal M. Hamed, Ameen Y. Al-Garawi 2. Effect of the Degree of canal Moisture on the Fracture Resistance of Endodontically Treated Teeth Roots Using Different Sealers (In Vitro Study) Dr. Alaa Abdulrahman Alomar, Prof. Hassan Alhalabiah 3. The Impact of Nurses’ Knowledge and Self-Efficacy on Quality of Life and Symptom Burden for Patients with Gastric Cancer Receiving Palliative Care in Jordan: A Review of Literature Dr. Nizar Adnan Rfefan Ass’ad 4. PCOS: Causes and treatment Dr. Souad Fareg Mohammd Dadoush 5. The effect of celecoxib on kidney function in elderly people in the Saudi health sector Dr. Hela Saleh Al-Khulaifi, Nurse Tala Saeed Al-Mutairi, Nurse Norah Ibrahim Al-Battal